Djetinjstvo u Agramu 1902-1903. M. Krleže i ideja djetinjstva - Benčić, Živa (1997)
Krleža's concept of childhood should be analised in the context of an idea that was elaborated from Rousseau onward by different European thinkers and artists. According to this idea, the child lives in a special dimension of reality, intact by pragmatic interests and rational schemes and thus more authentic than the "worn out, fragmented and bare reality" of the adult world. Krleža, like his predecessors, is primarily interested in those aspects of the child's psyche that allow analogies with the artist (spontaneity, freedom from the repressive mechanisms of culture, tendency to play, acceptance of the world in the pureness of sensual perception, etc.), which, at the same time, contribute to fuller understanding of his artistic position.
Projekt MZOS
HRV